2001
DOI: 10.1021/jf0100651
|View full text |Cite
|
Sign up to set email alerts
|

Assay of Ochratoxin A in Wine and Beer by High-Pressure Liquid Chromatography Photodiode Array and Gas Chromatography Mass Selective Detection

Abstract: To routinely assay the concentrations of ochratoxin A (OTA) in wines and beers, two new methods were developed and evaluated. The first utilized solid-phase extraction on a C(18) cartridge to achieve a 100-fold sample concentration followed by high-performance liquid chromatography on a C(18) column with gradient elution and quantitation at 333 nm by means of a photodiode array detector. Positive confirmation can be carried out by purity and match-factor analysis as well as peak shift following esterification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(108 citation statements)
references
References 41 publications
2
102
0
4
Order By: Relevance
“…VISCONTI et al 53 analyzed Italian and imported beers (61 samples) and found that half of the samples contained OTA in concentrations from <0.01 to 0.135 ng.mL -1 . No correlation between the incidences of OTA and country or beverage type was found by SOLEAS et al 42 in beer commercialized in Canada (107 samples). In Belgium, OTA was found by TANGNI et al 47 in all samples of 62 Belgian and 20 imported beers analyzed and the highest concentration was 0.185 ng.mL -1 .…”
Section: Introductionmentioning
confidence: 78%
“…VISCONTI et al 53 analyzed Italian and imported beers (61 samples) and found that half of the samples contained OTA in concentrations from <0.01 to 0.135 ng.mL -1 . No correlation between the incidences of OTA and country or beverage type was found by SOLEAS et al 42 in beer commercialized in Canada (107 samples). In Belgium, OTA was found by TANGNI et al 47 in all samples of 62 Belgian and 20 imported beers analyzed and the highest concentration was 0.185 ng.mL -1 .…”
Section: Introductionmentioning
confidence: 78%
“…In Portugal, Festas et al [189] did not find OTA in 64 domestic wines, but Soleas et al [160] detected it in five out of 37 samples of Portuguese wine. A survey of 340 Portuguese wines revealed that OTA was detectable in 20.3% of the samples and the highest level was 2.1 ng/mL [190].…”
Section: Occurrence Of Ota In Winementioning
confidence: 99%
“…Other enzymes which can be obtained from A. niger strains and which can efficiently degrade OTA are lipases 111 , an enzymatic crude protease 3 and a metalloenzyme 4 . A carboxypeptidase present in Phaffia rhodozyma can also degrade OTA up to 90% 7,84 .…”
Section: Detoxification Of Ochratoxin Amentioning
confidence: 99%